Assessing therapeutic potential of molecules: molecular property diagnostic suite for tuberculosis - Gaur, A. S.; Bhardwaj, A.; Sharma, A.; John, L.; Vivek, M. R.; Tripathi, N.; Bharatam, P. V.; Kumar, R.; Janardhan, S.; Mori, A.; Banerji, A.; Lynn, A. M.; et al. (Journal of Chemical Sciences, 2017)
Abstract: Molecular Property Diagnostic Suite (MPDS TB) is a web tool (http://mpds.osdd.net) designed to assist the in silico drug discovery attempts towards Mycobacterium tuberculosis (Mtb). MPDS TB tool has nine modules which are classified into data library (1–3), data processing (4–5) and data analysis (6–9). Module 1 is a repository of literature and related information available on the Mtb. Module 2 deals with the protein target analysis of the chosen disease area. Module 3 is the compound library consisting of 110.31 million unique molecules generated from public domain databases and custom designed search tools. Module 4 contains tools for chemical file format conversions and 2D to 3D coordinate conversions. Module 5 helps in calculating the molecular descriptors. Module 6 specifically handles QSAR model development tools using descriptors generated in the Module 5. Module 7 integrates the AutoDock Vina algorithm for docking, while module 8 provides screening filters. Module 9 provides the necessary visualization tools for both small and large molecules. The workflow-based open source web portal, MPDS TB 1.0.1 can be a potential enabler for scientists engaged in drug discovery in general and in anti-TB research in particular. Graphical Abstract: SYNOPSIS: A web-based MPDS TB Galaxy tool is developed for assessing therapeutic potential of molecules. MPDS TB is categorized into Data Library, Data Processing and Data Analysis. It can be a potential enabler for scientists engaged in drug discovery in general and in anti-TB research in particular. [Figure not available: see fulltext.] © 2017, Indian Academy of Sciences.
Keywords: chemical analysis; Chemoinformatics; computational chemistry; Diagnosis; Drug discovery portal; Information analysis; Libraries; Molecular graphics; Molecules; Neglected diseases; Open science; Portals; tuberculosis; Web-based technology; Websites